The Rhythmic Structure in the Poetry of Muhammad Saeed Al-Habouby - Alsowialy, Pro.Dr Haitham Abbas Salim; Ghayyadh, Sherine Kadhim (Thi Qar Arts Journal, 2021)
The poetry band of the core elements of the basic ingredients in poetry in every time and place, as a non-starter for the poetry without it, and that music was not aware of their impact and their impact in the soul unless interacted with the rest of the elements of the poetic experience in the same poet Mvlq, has promised a pot of hair; because it is an essential element can not be exceeded in any case, it is which highlights the features of the poem and its impact on the recipient and Matvolh in the hearts and souls of the impact of the sentimental, interacts with and responds to music sequential Ngmha.      Mediated music internal poet trying to create a consensus   psychologically between him and the world issued, poet and Maimer him from the  experiences and cases of psychological impact is readily visible in the folds of his hair, as per the same music of the Interior, and uses Habboubi that music and Mavera of the characteristics and features; to give the text beautiful and powerful as Using other rhetorical repetition, colors and Mavera means to suggest voice and rhythm, which produces psychological tremor.